Determinants of the Health and Well-Being of Adolescents (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Unfavorable trends in the health of the adolescent contingent cause an urgent need to consider morbidity and social well-being as one of the most significant risk factors of modern changes in demographic behavior and generational change directly in the family, which largely determine the specifics of the needs of adolescents in medical and social care.The article substantiates the relevance of the problem of preserving, strengthening and shaping the health of adolescents in the process of their education and upbringing.